Resilient Investments in a Fragmented World Trade Conflicts, Environmental Governance, and the Future of Sustainable Growth - Sri Eka NurBasmawati; Andi Aswan; Abdul Rahman Laba (Entrepreneurship Undergraduate Program at Amkop Business School, 2026)
Traditional investment models that prioritize efficiency and cost minimization are becoming increasingly vulnerable to supply chain disruptions, regulatory uncertainty, and climate-related risks. This study aims to examine the interrelationship between trade conflicts, environmental governance, and resilient investment strategies in promoting sustainable economic growth. Using a qualitative approach based on an extensive review of academic literature, international policy reports, and empirical evidence, the study explores how governments, businesses, and financial institutions adapt investment decisions in response to evolving geopolitical and environmental conditions. The findings indicate that resilient investments are characterized by supply chain diversification, strategic resource allocation, technological innovation, and the integration of Environmental, Social, and Governance (ESG) principles. Environmental governance, through climate policies, sustainability regulations, and green finance initiatives, plays a crucial role in redirecting capital toward low-carbon and environmentally responsible sectors. Meanwhile, trade conflicts encourage firms to strengthen regional production networks and reduce dependence on high-risk markets, thereby enhancing long-term investment resilience. The study further reveals that resilient investment serves not only as a mechanism for mitigating economic and geopolitical risks but also as a strategic instrument for achieving sustainable development objectives. The research contributes to the growing literature by providing an integrated framework that connects trade fragmentation, environmental governance, and investment resilience within the broader context of sustainable economic transformation. The findings offer practical implications for policymakers, investors, and multinational corporations in designing adaptive investment strategies capable of supporting inclusive, competitive, and environmentally sustainable growth in an increasingly uncertain global economy.Keywords: resilient investment; trade conflicts; geopolitical fragmentation; environmental governance; sustainable finance; ESG; sustainable growth; green investment